Clusterbean A boon crop for dry regions - Pathak, Rakesh; Roy, M. M. (Indian Farming, 2015)
Clusterbean is a valuable resource of income in arid and semi-arid parts of our country. It requires less care and inputs and gives much higher returns to the farmers and industries. The gum extracted from its seeds is eco-friendly and safe for using in different industries including food industry. As the popularity of clusterbean increases, this versatile crop is found to play important role in providing higher economic returns for small scale farmers in arid and semi-arid regions of our country. There is a great scope of its cultivation on larger areas with proven gum varieties for harnessing more profits.